The Privatization of Health Care System in Saudi Arabia - Redwanur Rahman (SAGE Publishing, 2020)
Saudi Arabia's Vision 2030 highlights the development of the health care sector through privatization. This study examines the factors that prompted the privatization of the health care sector in Saudi Arabia. This is a scoping review based on an extensive review of both published and unpublished documents. We have accessed different search engines and databases to collect various research publications, journal articles, government reports, policy and planning documents, and relevant press reports/articles. While privatization of the health care sector in Saudi Arabia has experienced an upward trend, the public health care sector remains vital to bring in overall improvements in the health of all sections of Saudi Arabia's population. Keeping this in view, the government must strengthen its public health care sector to ensure affordable, accessible, and high-quality health care for all. This manuscript focuses on the policy aspect of the privatization of health care and is based on secondary research material. Increased privatization leads to rising expenses in health care, while adversely affecting equity and accountability in the provision of its services. Although this study is an independent analysis of Saudi Arabia's health care system, lessons learned from this context could be used widely for policy-making in other countries with similar socioeconomic settings.